2021
DOI: 10.1037/dev0001245
|View full text |Cite
|
Sign up to set email alerts
|

Musical instrument engagement in adolescence predicts verbal ability 4 years later: A twin and adoption study.

Abstract: Individual differences in music traits are heritable and correlated with the development of cognitive and communication skills, but little is known about whether diverse modes of music engagement (e.g., playing instruments vs. singing) reflect similar underlying genetic/environmental influences. Moreover, the biological etiology underlying the relationship between musicality and childhood language development is poorly understood. Here we explored genetic and environmental associations between music engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
(149 reference statements)
3
8
0
Order By: Relevance
“…For instance, results of a recent twin study ( Wesseldijk et al, 2021 ) suggest that associations between music training and verbal skills can be explained by individual differences in music aptitude, that are partly driven by familial effects, suggesting shared genetic predispositions between music training and verbal skills. Another recent family-based study ( Gustavson et al, 2021 ) also suggests a genetic link between music engagement (skills, interest, lessons) and language development, in line with the framework proposed by Nayak et al (2022) . The interplay between genetic and environmental factors in the relationships between DLD status, musical training, and slowest motor tempo should be investigated in the future.…”
Section: Discussionsupporting
confidence: 60%
“…For instance, results of a recent twin study ( Wesseldijk et al, 2021 ) suggest that associations between music training and verbal skills can be explained by individual differences in music aptitude, that are partly driven by familial effects, suggesting shared genetic predispositions between music training and verbal skills. Another recent family-based study ( Gustavson et al, 2021 ) also suggests a genetic link between music engagement (skills, interest, lessons) and language development, in line with the framework proposed by Nayak et al (2022) . The interplay between genetic and environmental factors in the relationships between DLD status, musical training, and slowest motor tempo should be investigated in the future.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, twin and family-based studies show that musical abilities (e.g., pitch and rhythm sensitivity) have a significant genetic component ( Drayna et al, 2001 ; Seesjärvi et al, 2016 ; Ullén et al, 2014 ), as does musical engagement, including accomplishment and training ( Hambrick & Tucker-Drob, 2014 ), as summarized in Table 2 . Emerging evidence also finds that both musical aptitude and engagement are genetically associated with language-related traits such as verbal ability ( Gustavson et al, 2021 ; Wesseldijk et al, 2021 ).…”
Section: Heritability Of Speech-language and Musicality Phenotypesmentioning
confidence: 99%
“…One example of the utilization of twin and family studies to examine the associations between musicality and language comes from Gustavson et al (2021) , who find that self-reported musical instrument engagement at age 12 predicts verbal ability at age 16, controlling for IQ, and that this relationship is likely explained by shared genetic influences. Further, Wesseldijk et al (2021) report recent findings in twins that demonstrate that phenotypic associations between musical aptitude and vocabulary skills are partially attributable to shared family influences.…”
Section: Integrating Genetics Approaches Into Musicality-language Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the present study upholds previous observations that rhythm and grammar performance are indeed correlated, we did not delve into the neural, biological, or genetic mechanisms that are responsible for this association. Recent twin studies, for example, have revealed that shared genetic influences account for much of the association between verbal ability and measures of musical aptitude and music engagement 60 , 61 . Such findings are more consistent with a model in which musical and language traits are influenced by a similar set of genetic (and environmental) factors, rather than causal associations of music on language development.…”
Section: Discussionmentioning
confidence: 99%